Financial development, foreign direct investment and economic growth in Sri Lanka. (1st January 2014) - Jahfer, Athambawa; Inoue, Tohru
This paper examines the relationship between the financial development, foreign direct investment and economic growth in Sri Lanka using quarterly data over the period 1996 to 2011. Johansen co-integration technique and vector error correction model are used to investigate the relationships. The results demonstrate that there is a long-run equilibrium relationship and that there is bi-directional causality between the financial development and economic growth. Further, economic growth and financial development causes foreign direct investment, but no strong evidence that FDI causes economic development. Moreover, major implication of our findings is that financial development matters for the economic growth of Sri Lanka than foreign direct investment.